Anatomic, tomographic and sonographic study of podotrochlear apparatus of adult horses - Souza, L. P.; Bortolini, Z. [UNESP]; Mueller, T. R.; Fonteque, J. H.; Schade, J.; Luciani, M. G.; Souza, D. S.; Vulcano, L. C. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
The navicular syndrome is a condition involving the podotrochlear apparatus and represents one of the most common causes of forelimb lameness in horses. Therefore, further study of this region is of interest when it comes to diagnosis and treatment of lameness in horses. The aim of this study was to demonstrate the differences between the imaging findings of ultrasonography and computed tomography in the evaluation of the palmar structures of the podotrochlear apparatus of healthy adult horses and description of the structures observed in images obtained with these techniques. For this, four images of four anatomical parts were performed, and subsequently sectioned and used for the anatomical description. The use of anatomical parts helps in the understanding of normal anatomy leading to a better interpretation of the images and increasing the specificity of the diagnostic for detecting changes that cause diseases. Ultrasonography provides relevant information about these structures to be studied and the association with computed tomography (CT) increased the accuracy of the investigation. Despite the use of CT being more suitable for bone tissue it provides important information and can be used as a useful tool when there is no available MRI.
Keywords: diagnosis; lameness; navicular; computed tomography; ultrasound